The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1108/03074800810910478
|View full text |Cite
|
Sign up to set email alerts
|

Creating the next generation of library leaders

Abstract: PurposeThe paper aims to answer the question: “Where is our profession going and who is leading us there?”Design/methodology/approachThe article presents results of a survey directed to leadership institute attendees and attempts to determine the impact of such institutes on librarians' careers, and their willingness to move into administrative positions (department head, director, etc.) or leadership roles (project leader, committee chair). This paper was developed from the poster session, “Follow Me! Are Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
0
9
1
Order By: Relevance
“…It is said that the profession is 'greying' and that there are insufficient numbers of librarians both willing and prepared to take on leadership roles within individual libraries and the profession more generally (Arnold, Nickel and Williams 2008). Usherwood, Proctor and Bower (2001), for example, in a study of the UK public library workforce found a general consensus that there was a lack of leadership in the public library profession and no clear understanding of how the next generation of leaders could be fostered.…”
Section: Introductionmentioning
confidence: 99%
“…It is said that the profession is 'greying' and that there are insufficient numbers of librarians both willing and prepared to take on leadership roles within individual libraries and the profession more generally (Arnold, Nickel and Williams 2008). Usherwood, Proctor and Bower (2001), for example, in a study of the UK public library workforce found a general consensus that there was a lack of leadership in the public library profession and no clear understanding of how the next generation of leaders could be fostered.…”
Section: Introductionmentioning
confidence: 99%
“…For mid-career librarians, mentoring is often associated with leadership roles or the advancement to different positions in the organization. 31 It should be noted, however, that not all librarians have a desire to advance to roles of managers or administrators; instead, they may be motivated by leadership opportunities for project planning and special assignments. 32 Regardless, Hicks outlines problems that may arise when mentoring is used for developing.…”
Section: Mentoring and Leadershipmentioning
confidence: 99%
“…The evaluations specifically identify some content elements as being perceived by the participant as particularly relevant to his or her needs. Mentoring, networking and connecting with peers were perceived to be important to leadership development (Arnold, Nickel & Williams, 2008;Barney, 2003;Bonnici, 2001;Brockmeyer-Klebaum, 2000;Sheehy, 2004; The Center for Creative Leadership, 2008), but these activities needed to persist after the program concluded (Bonnici, 2001;BrockmeyerKlebaum, 2000). Program elements relating to organizational change were also important (The Center for Creative Leadership, 2008).…”
Section: Unfortunately Only One Of the Programs Executive Leadershimentioning
confidence: 99%
“…o Networking -essential to connecting with peers and relationship building (Arnold, Nickel & Williams, 2008;Barney, 2003;Bonnici, 2001;Brockmeyer-Klebaum, 2000;Sheehy, 2004 o Experiential assignment or project -ability to practise skills and use knowledge in the real world is essential to ensuring that the skills are transferred (Allio, 2006;Crosbie, 2005); o Continuing contact with mentors and other participants;…”
Section: Program Foundationmentioning
confidence: 99%
See 1 more Smart Citation